Public Policy and Poverty Reduction in the Arab Region - Fan, Shenggen; Ali, Ali Abdel Gadir (Arab Planning Institute, 2007)
The percentage of the world’s poor living below $1 per day fell by nearly a half in the last two decades of the 20th century. However, reduction in global poverty has been uneven across and within regions of the developing world. While the dramatic progress made in East Asia -- especially China -- is well-known, poverty indicators elsewhere have proven more fixed. This asymmetrical development story also holds true for the Arab countries.